Security in robot operating system (ROS) by using Advanced Encryption Standard (AES) - Nor Alia Syuhada, Shaharudin (2018)
As robotic systems spread, cybersecurity emerges as major concern. Currently, most research autonomous systems are built using the ROS framework which has become the most popular framework for developing robotic applications along with other commercial software. ROS is a distributed framework where nodes publish information that other nodes consume. This model simplifies data communication but poses a major threat because a malicious process could easily interfere the communications, read private messages, or even take over the robots movement. The study investigates a robot’s performance when ciphering the messages interchanged between ROS nodes under the publish/subscribe paradigm. In particular, this research focuses on using encryption algorithm which is AES. The encryption algorithm will be evaluated according to the performance of the system, both from computing and communications point of view.